ADAPTIVE LQR COURSE-KEEPING CONTROLLER FOR THE NONLINEAR MIMO MODEL OF A CONTAINER VESSEL - Brasel, Michał (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2014)
In the paper an adaptive control system for the nonlinear 4-DoF model of a container vessel is presented. The considered model of the ship includes input signals saturations and dynamics of actuators. Main goal of the presented control system is control of the course angle and speed of the ship relative to water. The system synthesis is carried out by means of LQ-optimal control method. Sets of controller parameters are designed using linearization of the considered model in the nominal steady-state operating points of the ship. The final part of the paper includes simulation results of control system operation with full nonlinear MIMO model of the container vessel.